Selimut Fototerapi LED—Solusi Inovatif Berbasis Keluarga dalam Mengatasi Kesenjangan Tatalaksana Ikterus Neonatorum - Tubagus Ferdi Fadilah (Jurnal Biomedika dan Kesehatan, 2026)
Neonatal jaundice remains the most prevalent clinical condition affecting newborns globally, impacting approximately 60% of term and 80% of preterm infants within the first week of life. For more than five decades, conventional phototherapy has served as the gold standard for preventing kernicterus secondary to severe hyperbilirubinemia. Despite its proven efficacy, the traditional hospital-based phototherapy model presents substantial public health challenges, particularly in developing countries such as Indonesia. Dependence on fixed, high-cost equipment within tertiary facilities often necessitates maternal–infant separation, disrupts early bonding and breastfeeding, and contributes to inequities in healthcare access based on geographic and socioeconomic factors. Technological advancements in Light Emitting Diode (LED) phototherapy blankets represent a paradigm shift toward family-centered neonatal care. By incorporating blue-green light sources into flexible, portable devices, these blankets enable effective treatment while maintaining skin-to-skin contact and direct breastfeeding. This approach supports maternal–infant attachment, enhances lactation success, and may facilitate bilirubin reduction through improved enteral feeding. From a public health perspective, LED phototherapy blankets promote decentralized care delivery by enabling deployment in primary healthcare facilities and remote settings, thereby reducing referral burden and treatment delays. Local innovations such as the BLUI Blanket demonstrate promising clinical efficacy and adherence to thermal safety standards, supporting their role as safe and effective first-line interventions. Furthermore, implementing home-based phototherapy programs for uncomplicated cases can reduce hospitalization costs, minimize the risk of nosocomial infections, and optimize hospital resource allocation. In conclusion, LED phototherapy blankets constitute a transformative innovation that integrates clinical effectiveness, psychosocial well-being, and health system efficiency. Their broader adoption has the potential to enhance equitable neonatal care delivery while preserving the integrity of the mother–infant dyad.